2018
DOI: 10.1016/j.chiabu.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The grip of trauma: How trauma disrupts the academic aspirations of foster youth

Abstract: The academic challenges foster youth encounter during their P-12 education have been widely reported. Yet, despite these challenges, the majority of foster youth desire postsecondary education. What is less known is the reason why so few foster youth alumni who desire a four-year college degree, achieve this goal. For the participants in this four-year longitudinal study, maltreatment, resulting in foster care placement, and the ensuing exposure to the foster care system, resulted in trauma histories and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 26 publications
1
35
0
2
Order By: Relevance
“…Our themes reinforce prior findings that these students may experience persistent mental health challenges related to their foster care involvement, which may inhibit college success if not specifically addressed. 9,10,5,3,7 Our study also confirms both the potential tension of self-reliance versus interdependence among college students with foster care histories, as well as the related challenge of successfully finding support that attends to their specific lived experiences and present needs. 8 Students in this study were more likely to engage with campus-based services that are individualized and provided by support people -including faculty, staff, and counselors -who understand their lived experiences and foster care background and thus offer a "safe" and trustworthy resource to explain their personal story to or to develop a relationship with as they navigate college challenges.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our themes reinforce prior findings that these students may experience persistent mental health challenges related to their foster care involvement, which may inhibit college success if not specifically addressed. 9,10,5,3,7 Our study also confirms both the potential tension of self-reliance versus interdependence among college students with foster care histories, as well as the related challenge of successfully finding support that attends to their specific lived experiences and present needs. 8 Students in this study were more likely to engage with campus-based services that are individualized and provided by support people -including faculty, staff, and counselors -who understand their lived experiences and foster care background and thus offer a "safe" and trustworthy resource to explain their personal story to or to develop a relationship with as they navigate college challenges.…”
Section: Discussionsupporting
confidence: 66%
“…Recent studies have shown that students transitioning from foster care can struggle with the psychological effects of past trauma as they move into and through post-secondary education. 3,4 Further studies have shown that students with foster care histories have themselves identified mental health challenges during the transition from high school to college, noting the importance of access to appropriate mental health services and suggesting that mental health challenges that go unresolved could be a cause of students leaving school. 5 Among those who do enroll in postsecondary education, students with foster care backgrounds have a 34% dropout rate compared to 18% among similar low-income and first-generation students, 6 and this relative dropout rate was more recently reported as 28% versus 12%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We do know that consistent coaching to increase the application of self-determination skills can improve outcomes, for example by teaching youth how to lead their own transition planning meetings (e.g., Powers et al, 2012; Powers et al, 2018). However, skill-building strategies to facilitate supportive ties to service providers and other formal resources must account for youth readiness to invest in these relationships, given prior experiences influencing mental health and attachment (e.g., impacting post-secondary outcomes: Morton, 2018; Okpych & Courtney, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…This kind of “survivalist self-reliance” (Samuels & Pryce, 2008) is not uncommon when young people exit care lacking more normative experiences of social development and community integration (e.g., Pryce, Napolitano, & Samuels, 2017). This has also recently been explored in terms of the effect of trauma-related mental health diagnoses (Morton, 2018) and the development of avoidant attachment styles (Okpych & Courtney, 2018) specifically impacting post-secondary achievement among former foster youth.…”
Section: Introductionmentioning
confidence: 99%